High Prevalence of Orodental Disorders in South Brazilian Cart Horses: Walking a Tightrope Between Animal Welfare and Socioeconomic Inevitability - Kunz J.R.* (2020)
© The Author(s) 2020.In developing and emerging countries, many people make a living from picking municipal solid waste to sell for reuse or recycling. These people depend on cost-effective transport vehicles like horse-drawn carts. It is indisputable that the general health of these horses not only plays a major economic role but is a welfare issue as well. Orodental disorders are likely to be of particular importance as they directly impair health, performance, and therefore influence animal welfare and income. However, studies investigating prevalence and distribution of orodental disorders in working horses are scarce. This cross-sectional study is a survey of orodental alterations in 70 South Brazilian urban mixed-breed cart horses. All animals were subjected to a standardized clinical and subsequent specific orodental examination, and no horse had previously received dental treatment. Age and gender-related distribution and correlation of type and prevalence of orodental disorders were assessed. Excessively sharp enamel points (98.6%), cheek tooth diastema (65.7%), and mucosal ulcers (65.7%) occurred most frequently. Diastemata were more likely to be present between maxillary and mandibular Triadan 06/07 and mandibular 10/11. Male horses showed a higher individual number of orodental alterations than females (P =.048). Incisors were often worn down and endodontically affected, occurring most frequently in horses >18 years (P =.004) and males (P =.048). Results indicate a high prevalence of orodental changes among South Brazilian cart horses. Poor orodental health in working horses is an animal welfare issue and may be influenced by the socioeconomic status of waste pickers.